The organization and function of the Golgi apparatus in dendrite development and neurological disorders - Chen, Meilan; Xu, Lu; Wu, Yi; Soba, Peter; Hu, Chun (Genes & Diseases, 2023)
Dendrites are specialized neuronal compartments that sense, integrate and transfer information in the neural network. Their development is tightly controlled and abnormal dendrite morphogenesis is strongly linked to neurological disorders. While dendritic morphology ranges from relatively simple to extremely complex for a specified neuron, either requires a functional secretory pathway to continually replenish proteins and lipids to meet dendritic growth demands. The Golgi apparatus occupies the center of the secretory pathway and is regulating posttranslational modifications, sorting, transport, and signal transduction, as well as acting as a non-centrosomal microtubule organization center. The neuronal Golgi apparatus shares common features with Golgi in other eukaryotic cell types but also forms distinct structures known as Golgi outposts that specifically localize in dendrites. However, the organization and function of Golgi in dendrite development and its impact on neurological disorders is just emerging and so far lacks a systematic summary. We describe the organization of the Golgi apparatus in neurons, review the current understanding of Golgi function in dendritic morphogenesis, and discuss the current challenges and future directions.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Dendrite; Golgi; Golgi outposts; Microtubule; Neurodevelopmental disorders; Secretory pathway